Horizons of the Integration among ( SEN&SAD ) Group of the Countries - Al Farsi, Dr.Essa Hamad; Al-Majbri, Dr.Fathi Abdel Hafeez (Dirasat in Economics and Business, 2002)
Economic integration may be considered as one of the most important conceptions of our time. The European, Latin American, Asian, African, are examples of that reality. The ( SEN&SAD) countries aimed to attain several economic and non-economic objectives. One of the most important of these is to increase interregional trade and foster economic development. In order to show the importance of this step toward economic integration, this paper has defined the aims and concepts of economic integration of the ( SEN&SDA) countries. The paper further explains the importance and necessary interaction between the ( SEN&SDA) countries and African Union. To achieve this, the paper has been organized as follows. Section one provides some theoretical background for the economic integration. In section tow, definition of the ( SEN&SDA) countries and its structural. Section three, characteristics of the ( SEN&SDA) countries. Final section provides some conclusions, which should be taken into consideration in economic integration.